Hephaestus and Athena (Signifiances (Signifying), 2022)
The text aims at outlining the guidelines of the issue of Signifiances (Signifying) 5 entitled Semiotic Dynamics and Linguistics of Individuals, whose contributions have in common a focus on the experience and strategies of concrete speaking subjects. This leads the authors to positions that are often close to the sociological currents that have emerged as a counterpoint to the Durkheimian frame of reference. More generally, displayed empiricist stances in several contributions bear witness to the forgotten heritage of the Empirical (Herbartian) Psychology, which was one of Saussure's indirect sources. The theses themselves present several points of convergence, in particular as regards the recognition of specific forms of reflexivity in the speaking subject and, correlatively, the limits of traditional categories when it comes to describing real language activity. Most analyses therefore hypothesise a de facto dichotomy between the knowledge of speaking subjects and the metalanguage of science, and between individual experiences and collective meanings. They thus address the two central sociological issues of the status of social norms and the modelling of the relationship between individual and society.